2017
DOI: 10.1177/0305735617705007
|View full text |Cite
|
Sign up to set email alerts
|

Self-affirmation improves music performance among performers high on the impulsivity dimension of sensation seeking

Abstract: In the light of evidence that self-affirmation can mitigate the negative effects of stress on outcomes, this study tested whether a self-affirmation manipulation could improve undergraduate students' achievement in a formal musical performance examination. The study also investigated the association between impulsivity and music performance and explored whether impulsivity moderated any impact of selfaffirmation on exam performance. Methods: At baseline, participants provided demographic information and comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…In fact, there is a difference between the willingness to sensation seek and its expression in terms of behavior, and it is very likely that the willingness to sensation seek is more easily expressed in individualistic cultures, where social pressure, hierarchy, power distance, and conformism are very important (Hofstede, 1991). This could explain why sensation seeking, which may be associated with self-affirmation (Churchill et al, 2018), failed to be related to SPE. Another explanation could be that sensation seeking is a composite of four distinct characteristics-adventure seeking, experience seeking, disinhibition and susceptibility/impulsivity- (Aluja et al, 2019), whose respective contributions to SPE are still unclear and need to be elucidated and clarified.…”
Section: Contribution Of Normal and Malevolent Personality Traits To mentioning
confidence: 99%
“…In fact, there is a difference between the willingness to sensation seek and its expression in terms of behavior, and it is very likely that the willingness to sensation seek is more easily expressed in individualistic cultures, where social pressure, hierarchy, power distance, and conformism are very important (Hofstede, 1991). This could explain why sensation seeking, which may be associated with self-affirmation (Churchill et al, 2018), failed to be related to SPE. Another explanation could be that sensation seeking is a composite of four distinct characteristics-adventure seeking, experience seeking, disinhibition and susceptibility/impulsivity- (Aluja et al, 2019), whose respective contributions to SPE are still unclear and need to be elucidated and clarified.…”
Section: Contribution Of Normal and Malevolent Personality Traits To mentioning
confidence: 99%
“…In terms of controlling for confounding factors, the majority of studies addressed at least 80% of the relevant factors (strong). Seventeen studies [ 23 , 41 , 45 , 46 , 49 , 50 , 51 , 55 , 57 , 59 , 61 , 68 , 109 , 121 , 124 , 128 , 134 ] indicated that evaluators and/or participants were aware of the research objectives (weak). Similarly, most studies employed validated and reliable data collection tools (strong).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies also had low performance bias and detection bias, as both participants and personnel were blind to the experimental condition ( Blinding of participants and personnel ) in most cases, as were outcome assessors ( Blinding of outcome assessment ). Seven studies (Baker et al., 2019; Bancroft et al., 2017; Bratter et al., 2016; Churchill et al., 2018; Kost‐Smith et al., 2012; Peters et al., 2017; Rapa, 2016) had a high risk of attrition bias due to incomplete outcome data either overall or in one condition relative to another ( Incomplete outcome data ). Interestingly, these high‐risk studies yielded a small and nonsignificant average affirmation effect ( g = .05, 95% CI [−.14, .24], p = .626), while the low‐risk and the unclear‐risk studies had medium and significant average affirmation effect ( low : g = .11, 95% CI [.03, .20], p = .012; unclear : g = .25, 95% CI [.15, .34], p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies did not specify a targeted identity‐threatened group and reported only the main affirmation effect for all sampled students and did not provide extractable information on whether the effect differed by students’ group status (Churchill et al., 2018; De Clercq et al., 2019; Lauer et al., 2013; Peters et al., 2017; Rapa, 2016). Because we could not combine these effects with the pooled estimated for either threatened or nonthreatened students, we excluded them in the calculations of the average affirmation effect (see Appendix for the calculation of average affirmation effect among this small subset of studies).…”
Section: Methodsmentioning
confidence: 99%